A Population Approach to Transportation Planning: Reducing Exposure to Motor-Vehicles. (13th June 2013) - Fuller, Daniel; Morency, Patrick
Abstract : Transportation planning and public health have important historical roots. To address common challenges, including road traffic fatalities, integration of theories and methods from both disciplines is required. This paper presents an overview of Geoffrey Rose's strategy of preventive medicine applied to road traffic fatalities. One of the basic principles of Rose's strategy is that a large number of people exposed to a small risk can generate more cases than a small number exposed to a high risk. Thus, interventions should address the large number of people exposed to the fundamental causes of diseases. Exposure to moving vehicles could be considered a fundamental cause of road traffic deaths and injuries. A global reduction in the amount of kilometers driven would result in a reduction of the likelihood of collisions for all road users. Public health and transportation research must critically appraise their practice and engage in informed dialogue with the objective of improving mobility and productivity while simultaneously reducing the public health burden of road deaths and injuries.